The Role Of Artificial Intelligence Technologies In Public Oversight And Expertise: Uzbekistan's Experience And International Practices - Shavkat Nazarov (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This article provides a systematic analysis of the role and capabilities of artificial intelligence technologies in public oversight and expertise processes. The research examines the experiences of developed countries such as Estonia, Singapore, and Germany in the field of digital public oversight. The activities of the «Regulation.gov.uz» and «Meningfikrim.uz» platforms implemented in Uzbekistan and ways to improve them are considered. The author substantiates the advantages of artificial intelligence in improving the quality of normative legal documents, ensuring transparency in decision-making processes, and expanding public participation. The article provides specific proposals for introducing amendments to the Law «On Normative Legal Documents».